The Core- and Pan-Genomic Analyses of the Genus Comamonas: From Environmental Adaptation to Potential Virulence - Wu, Yichao; Zaiden, Norazean; Cao, Bin (Frontiers in Microbiology, 2018)
Comamonas is often reported to be one of the major members of microbial communities in various natural and engineered environments. Versatile catabolic capabilities of Comamonas have been studied extensively in the last decade. In contrast, little is known about the ecological roles and adaptation of Comamonas in different environments as well as the virulence of potentially pathogenic Comamonas strains. In this study, we provide genomic insights into potential ecological roles and virulence of Comamonas by analysing the entire gene set (pangenome) and the genes present in all genomes (core genome) using thirty-four genomes of eleven different Comamonas species. The analyses revealed that the metabolic pathways that enable Comamonas to acquire energy from various nutrient sources are well conserved. Genes for denitrification and ammonification are abundant in Comamonas, suggesting that Comamonas plays an important role in the nitrogen biogeochemical cycle. They also encode sophisticated redox sensory systems and diverse c-di-GMP controlling systems, allowing them to be able to effectively adjust their biofilm lifestyle to changing environments. The virulence factors in Comamonas were found to be highly species-specific. The conserved strategies used by potentially pathogenic Comamonas for surface adherence, motility control, nutrient acquisition and stress tolerance were also revealed.